Protective factors in Chinese university students at clinical high risk for psychosis. (30th May 2016) - Shi, Jingyu; Wang, Lu; Yao, Yuhong; Chen, Fazhan; Su, Na; Zhao, Xudong; Zhan, Chenyu
Abstract: The role of protective factors in symptom formation and prognosis in schizophrenia has been shown in many studies, but research in the early phases of psychosis is limited, particularly among the nonclinical subjects. Protective factors associated with the severity of symptoms and clinical outcomes might be meaningful to the establishment of prevention systems and to the development of optimal psychosocial interventions prior to the onset of psychosis. The present study compares self-reported levels of self-esteem, social support and resilience of 32 university students at clinical high risk for psychosis (CHR) and 32 healthy controls in a longitudinal study design. Associations between protective factors with symptoms of psychosis were assessed in the CHR group. Individuals at CHR showed significantly lower self-esteem, social support and resilience compared to healthy controls. In the CHR group, lower social support and lower self-esteem were associated with more severe positive, negative and depressive symptoms. Multiple regression analyses revealed that self-esteem was the only significant determinant for negative, depressive symptoms and global functioning. In addition, we found that subjects who were fully recovered at a 6-month follow-up survey were greater resilient and showed lower depressive symptoms at baseline. The result implied that resilience intervention could be effective on early prevention of the onset of psychosis. Moreover, implications and limitations of this study will be discussed. Highlights: We screen out 32 CHR subjects from 2800 college students. They show lower self-esteem, social support and resilience than healthy control. Self-esteem significantly predicts severity of negative and depressive symptoms. Social support significantly predicts the severity of positive symptom. Resilience may be a potential protective factor preventing psychotic conversion.